2017
DOI: 10.3324/haematol.2017.169870
|View full text |Cite
|
Sign up to set email alerts
|

The role of constitutive activation of FMS-related tyrosine kinase-3 and NRas/KRas mutational status in infants with KMT2A -rearranged acute lymphoblastic leukemia

Abstract: Constitutive activation of the FMS-related tyrosine kinase-3 (FLT3) by mutations or high expression levels is common in acute leukemias.1 Aberrant FLT3 signaling is mediated via the RAS/MAPK and PI-3-Kinase/AKT pathways leading to proliferation, survival, and therapy resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
(8 reference statements)
0
6
1
Order By: Relevance
“…The CNS is involved in about 5% of MLLr BCP-ALL patients [66]. MLLr-ALL have frequent mutations in the RAS pathway [67][68][69], which as previously discussed was shown to be linked with an increased risk of CNS infiltration [44]. Furthermore, KRAS activation was shown to promote CNS infiltration of MLLr cells harboring the MLL-AF4 fusion gene [70].…”
Section: The Relevance Of Cytogeneticsmentioning
confidence: 82%
“…The CNS is involved in about 5% of MLLr BCP-ALL patients [66]. MLLr-ALL have frequent mutations in the RAS pathway [67][68][69], which as previously discussed was shown to be linked with an increased risk of CNS infiltration [44]. Furthermore, KRAS activation was shown to promote CNS infiltration of MLLr cells harboring the MLL-AF4 fusion gene [70].…”
Section: The Relevance Of Cytogeneticsmentioning
confidence: 82%
“…The mutational landscape of KMT2A r acute leukemia is well‐characterized overall. Of particular interest, variants within the PI3K‐RAS pathway have been identified in cases of KMT2A‐MLLT10 AML and B‐ALL across all age groups 55‐57 . One study also observed that inactivating mutations of PAX5 were more frequently associated with pediatric cases bearing KMT2A‐MLLT10 and KMT2A‐MLLT3 , compared with other KMT2A r 55 .…”
Section: Prognosis In Allmentioning
confidence: 99%
“…When activated by mutations, KRAS protein activates downstream cytosolic effectors including the RAF/MEK/ERK pathway and the PI3K/AKT/mTOR pathway to promote cell growth, proliferation, and survival 9 , 10 . The transforming protein that results is implicated in various malignancies, including lung adenocarcinoma 11 , colorectal cancer 12 , pancreatic cancer 13 , and leukemias 14 .…”
Section: Introductionmentioning
confidence: 99%